Mutant ATRX: pathogenesis of ATRX syndrome and cancer - Yuan, Kejia; Tang, Yan; Ding, Zexian; Peng, Lei; Zeng, Jinghua; Wu, Huaying; Yi, Qi (Frontiers in Molecular Biosciences, 2024)
The transcriptional regulator ATRX, a genetic factor, is associated with a range of disabilities, including intellectual, hematopoietic, skeletal, facial, and urogenital disabilities. ATRX mutations substantially contribute to the pathogenesis of ATRX syndrome and are frequently detected in gliomas and many other cancers. These mutations disrupt the organization, subcellular localization, and transcriptional activity of ATRX, leading to chromosomal instability and affecting interactions with key regulatory proteins such as DAXX, EZH2, and TERRA. ATRX also functions as a transcriptional regulator involved in the pathogenesis of neuronal disorders and various diseases. In conclusion, ATRX is a central protein whose abnormalities lead to multiple diseases.